Guía de recursos para la investigación antropológica. - Crespo, R.; Calle, S. de la; Albarrán, Mª José; Beloki, N.; Riera, N.; Padial, M. E.; Lázaro, L.; Gascón, D.; Redondo, A.; Santolaya, C.; Tercero, C. (Revista de Antropología Social, 1993)
Sin resumen